2002
DOI: 10.1074/jbc.m201726200
|View full text |Cite
|
Sign up to set email alerts
|

Microaerophilic Conditions Permit to Mimic in VitroEvents Occurring during in Vivo Helicobacter pylori Infection and to Identify Rho/Ras-associated Proteins in Cellular Signaling

Abstract: Molecular dissection of the mechanisms underlyingHelicobacter pylori infection suffers from the lack of in vitro systems mimicking in vivo observations. A system was developed whereby human epithelial cells (Caco-2) grown as polarized monolayers and bacteria can communicate with each other under culture conditions optimal for each partner. Caco-2 cells grown on filter supports were inserted in a vertical position into diffusion chambers equilibrated with air and 5% CO 2 at their basolateral surface (aerophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 64 publications
7
61
0
Order By: Relevance
“…20,21 Oxygen radicals were produced by the association of H. pylori with gastric epithelial cells. We previously demonstrated that lipid peroxidation, an index of oxidative membrane damage, increased by H. pylori in gastric epithelial AGS and Kato III cells, which was in parallel with a time-course stimulation of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Oxygen radicals were produced by the association of H. pylori with gastric epithelial cells. We previously demonstrated that lipid peroxidation, an index of oxidative membrane damage, increased by H. pylori in gastric epithelial AGS and Kato III cells, which was in parallel with a time-course stimulation of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a polarized Caco-2 cell monolayer at week 3 was established by morphology and monitoring of the transepithelial electrical resistance (TER; ohms ϫ cm 2 ) using a Millicell-ERS apparatus (Millipore, Bedford, MA). TER values of well-differentiated monolayers were in the range of 380 -450 ohms ϫ cm 2 (13). Bacterial Strains-The bacterial strains L. rhamnosus CGMCC 1.3724 and B. lactis CNCM I-3446 were obtained from the China general microbiological culture collection and Pasteur Institute microbiological culture collection, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of NF-B Nuclear Translocation and IB␣ Evaluation-Preparation of Caco-2 cell small-scale nuclear extracts and use in EMSA for the detection of NF-B was carried out as described in Cottet et al (13). The radioactivity associated with retarded oligonucleotide-NF-B complexes was quantified on an Instant Imager reader (Packard, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells cultivated up to 80% confluency were seeded on polyester Snapwell filters (diameter, 12 mm; pore size, 0.4 m; Corning Costar) at a density of 0.8 ϫ 10 5 cells/cm 2 . At week 3, the Caco-2 cell monolayer integrity was checked by measuring the TER using the Millicell-electrical resistance system (ERS) device (Millipore) (34). TER values of well differentiated monolayers were in the range of 400 -500 ohm/cm 2 .…”
Section: Preparation Of Human Plasma Iga- Igm-and Igg-enrichedmentioning
confidence: 99%